2015
DOI: 10.1002/app.41928
|View full text |Cite
|
Sign up to set email alerts
|

Migration resistant glucose esters as bioplasticizers for polylactide

Abstract: Environmental and sustainability issues have catalyzed efforts to replace traditional polymer additives with biobased alternatives. Glucose pentaacetate (GPA) and sucrose octaacetate (SOA) as model commercial saccharide esters and three synthesized glucose hexanoate esters (GHs) were evaluated as bioplasticizers for polylactide (PLA). For the GHs different reaction times were utilized to reach plasticizers with different number of hexanoate groups to establish how the degree of substitution influences miscibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…The larger reduction of T g shown in the present study could be explained by the lower T g (<−50 °C) of the synthesized PBSA plasticizer, which is caused by the combination of more flexible structure due to the adipic acid units and much lower molecular weight and agrees well with previous values reported for PLA plasticized with low molecular weight ester plasticizers [18,28]. Blending 20 wt % of glucose ester ( M n ≤ 1030 g/mol) with PLA could reduce T g to about 25 °C, which was 30 °C lower than the T g of neat PLA [28]. Blending PLA with 20 wt % oligomeric PHB led to a 29 °C decrease in T g while grafting the same amount of oligomeric PHB resulted in a 25 °C decreasing compared to neat PLA [18].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The larger reduction of T g shown in the present study could be explained by the lower T g (<−50 °C) of the synthesized PBSA plasticizer, which is caused by the combination of more flexible structure due to the adipic acid units and much lower molecular weight and agrees well with previous values reported for PLA plasticized with low molecular weight ester plasticizers [18,28]. Blending 20 wt % of glucose ester ( M n ≤ 1030 g/mol) with PLA could reduce T g to about 25 °C, which was 30 °C lower than the T g of neat PLA [28]. Blending PLA with 20 wt % oligomeric PHB led to a 29 °C decrease in T g while grafting the same amount of oligomeric PHB resulted in a 25 °C decreasing compared to neat PLA [18].…”
Section: Resultssupporting
confidence: 92%
“…Plasticizer migration resistance could also be improved when branched plasticizers were used [18,28,29,30]. It has been shown that blending PBSA into PLA could facilitate crystallization of PLA and mitigate the brittleness of PLA when the phase separation could be reduced by adding compatibilizer or annealing the blends [20,27].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the char residue was rich in O, P, C, and also contained N element. This was coincidence with the results of the FT-IR analysis of the condensed products at different temperatures [25].…”
Section: Thermal Degradation Mechanismsupporting
confidence: 90%
“…Notably,p erfect hollow spheres,t ubes, and fibers of conducting polymers are synthesized by controlling the synthesis approach. [38][39][40][41] In the present case, of interfacial polymerization, the redox reactionb asically occurs at the aqueous-organic interfacial region, as shown in Figure 1, where aC zi so xidized by oxidants APS or KMnO 4 with preferential concurrent doping of the NH group through as imple acid-base reaction. The NH group of Cz is expected to be ad riving force for the self-assembly of the polymer,s imilart ot he aggregation of polyaniline into hollow spheres.…”
Section: Resultsmentioning
confidence: 69%